The (Local) Rise and (Global) Fall of the “Coefficient of Racial Likeness” - Bréard, Andrea (ISIS, 2025)
The “Coefficient of Racial Likeness” (CRL) ascribed to Karl Pearson (1857–1936) was born in the Biometric Laboratory in London. It was developed with the purpose to determine the distance between two samples of different origins. Widely used but also distrusted before being ultimately replaced by a true statistical measure of divergence, the Mahalanobis distance (D2), the global biography of the CRL reveals the social, scientific, and historical forces at play that determined the lifespan of the coefficient, its success and fall from grace. Closely linked to Pearson personally, he could no longer control its fate once the CRL had escaped his laboratory and gotten into the hands of critical mathematicians, or to China where results of racial classification based on a single number and the assumption of homogeneity did not please the audienc